EFFECT OF BOARD SIZE ON THE FINANCIAL PERFORMANCE OF MERGED INSTITUTIONS - Ogada, Agnes; Achoki, George; Njuguna, Amos (American Journal of Finance, 2016)
Purpose: The purpose of this study was establishing the effect of board size on the financial performance of merged institutions. Methodology: The study adopted a mixed methodology research design. The study population included all the 51 merged financial service institutions in Kenya. Purposive sampling was used. Primary data was obtained from questionnaires and a secondary data collection template was also used. The researcher used quantitative techniques in analyzing the data. Descriptive analysis for the study included the use of means, frequencies and percentages. Inferential statistics such as correlation analysis was also used. Panel data analysis was also applied. Further, a pre and post merger analysis was used. Results: Board size had a significant relationship with financial performance of merged institution. Unique contribution to theory, practice and policy: It was recommended that, firms are place a remarkable degree of emphasis on the area of corporate governance and to some extent embark on eliminating CEO duality. The study also recommends a board size (6 and 8) for better financial performance. This will reduce the problem of free rider and enhance effective monitoring and decision making. It will also bring about cohesion among the board members.